Congenital Zika syndrome phenotype in a child born in Brazil in December 2011 - Coelho, Katia E. F. A. (Clin Case Rep, 2018)
We report a case of a Brazilian child born in 2011 with congenital Zika syndrome phenotype. Zika virus (ZIKV) may have been circulating in Brazil more than 4 years before the outbreak. ZIKV infection might be considered in children with this phenotype even without known circulation of ZIKV.